Digital Civilization and the Loss of the Sacred Dimension: The Relevance of Al-Ghazali's Thought in the Era of Artificial Intelligence. - Mulyana Mulyana (KASTA : Jurnal Ilmu Sosial, Agama, Budaya dan Terapan, 2026)
The development of Artificial Intelligence (AI) and digital technology has brought about significant transformations in various dimensions of human life. In addition to providing convenience, efficiency, and increased productivity, these developments have also given rise to the phenomenon of desacralization of life characterized by the weakening of spiritual values, the strengthening of instant culture, and the increasing materialistic orientation in society. This study aims to analyze this phenomenon through the perspective of Al-Ghazali's thought. The study uses library research methods with a philosophical and hermeneutical approach. The results of the study indicate that AI has the ability to increase the effectiveness of information processing and support various human activities, but lacks moral awareness, ethical responsibility, or a spiritual dimension. In this context, Al-Ghazali's thought, particularly the concept of tazkiyat al-nafs, offers a relevant ethical and spiritual framework to maintain a balance between technological progress and human values. Therefore, the development and utilization of AI need to be accompanied by strengthening aspects of ethics, morality, and transcendental awareness so that technological progress can provide sustainable benefits for human life.